Plants from Bulgarian Botanical Gardens: Some Selected Species with Potential for Health Food and Medical Applications - Aleksandra Ivanova; Stefka Bogdanova; Veselin Petrov; Tsanko Gechev (Plants)
Bulgarian botanical gardens harbor more than 3600 plant species from across the world. Some of them are well-known plants widely used by humans, others are underutilized crops or little-known exotic species. The latter group constitutes a rich reservoir of plant resources whose potential to bring benefits to society is still untapped. The aim of this review is to describe the diversity of species and their potentially valuable secondary metabolites in three of the largest Bulgarian botanical gardens, with a focus on underutilized crops and medicinal plants that are typical of Bulgaria. With this, we aim to pave the way for future research on the most promising of these plants. The report includes currently available ethnobotanical data on the properties and composition of their bioactive components, known culinary or therapeutic uses, and nutritional profiles. We also outline the vast potential of these plants in providing healthy diets, as well as for performing future groundbreaking biomedical research. Finally, we present the approach that will be used to screen extracts from these plants for biological activity.